PENGARUH PROFITABILITAS, SOLVABILITAS, LIKUIDITAS, DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI TERHADAP HARGA SAHAM - Oktavia Kumaralita; Rukmini Rukmini; Desy Nur Pratiwi (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the effect of profitability, solvency, and liquidity on the stock prices of food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024, with company size as a moderating variable. This study uses a quantitative approach with multiple linear regression analysis methods. The data used are secondary data in the form of annual financial reports from 40 companies selected through a purposive sampling method for three years, so that the total observation is 120 data. The independent variables studied include Return on Assets (ROA) as a proxy for profitability, Debt to Equity Ratio (DER) for solvency, and Current Ratio (CR) for liquidity. Company size is measured using the natural logarithm of total assets as a moderating variable, while stock price is the dependent variable. Before the regression analysis was carried out, the data were tested using the classical assumption test which includes the normality test (with Kolmogorov-Smirnov, histogram, and P-Plot), multicollinearity test, autocorrelation test (run test), and heteroscedasticity test (scatter plot). After the data meets the normality assumption and all classical assumptions are met. The results of the regression test show that: (1) profitability has a positive and significant effect on stock prices; (2) solvency does not have a significant effect on stock prices; (3) liquidity has a positive and significant effect on stock prices. In addition, the company size variable is able to significantly moderate the effect of profitability and liquidity on stock prices, but does not moderate the effect of solvency. This study contributes to investors in assessing financial performance as a basis for making investment decisions, as well as for companies in developing financial strategies to increase stock value.